Role of Myosin Heavy Chain Polymorphism in Differential Susceptibility of Muscle Fibers to Eccentric Contraction - Choi, Seung Jun (ProQuest Dissertations & Theses, 2011)
Relationships between myosin heavy chain (MHC) isoform content and eccentric-induced damage were investigated in chemically skinned muscle fiber segments. Fibers were subjected to an eccentric contraction standardized for strain magnitude (0.25 fiber length) and velocity (0.50 maximal shortening velocity). Fiber MHC isoform content was identified by SDS-PAGE. Pre- to post-eccentric changes in Ca2+-activated specific force, an accepted marker of damage, were analyzed using multiple linear regression. The first study utilized vastus lateralis (VL) fibers from young human subjects (25±2 yrs, N=10). When pre-specific force was held constant, fibers expressing type I or type IIa MHC showed identical post-eccentric force reductions while fibers co-expressing the type IIa and IIx MHC showed significantly greater force deficits. The limited number of monomorphic (type I, IIa) and polymorphic (type IIa/IIx) fibers in the human VL made it difficult to distinguish the role of MHC co-expression on these results. Therefore, in the second study, we utilized muscle fibers from C57BL/6 mice in order to examine the full range of mammalian MHC monomorphic (type I, IIa, IIx, IIb) and most common polymorphic (type I/IIa, IIa/IIx, IIx/IIb) fibers. Fibers expressing multiple MHC's showed a 3-fold greater post-eccentric force loss than fibers expressing a single MHC isoform. These studies point to an association between fiber MHC polymorphism and increased susceptibility of the myofilament lattice to high mechanical strain. Finally, we tested VL fibers from elderly subjects (78±2 yrs, N=8) in order to investigate how susceptibility to damage may be altered by age. Comparision to the young subjects of the first study revealed that resistance to eccentric-induced damage was preserved in type I fibers well into the 8 th decade of life. Likewise, type IIa/IIx fibers from young and old subjects showed similar susceptibility to damage. However, type IIa fibers from elderly subjects showed a 4-fold greater force reduction after the eccentric treatment. These results indicate a fiber type specific deterioration of the myofilament lattice with age. The novel findings of this research are the relative resistance of MHC monomorphic fibers and the greater susceptibility of MHC polymorphic fibers to eccentric damage and how these relationships are altered with aging.